PENERAPAN MODEL PEMBELAJARAN LANGSUNG MELALUI MEDIA POWER POINT UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI JURNAL PENUTUP DAN NERACA SALDO SETELAH PENUTUPAN - Titah Roshidah, ; Lusinta, (Pendidikan Ekonomi, 2012)
The purpose of this study is to find out the students activities, the teacher activities, students learning outcome and the students learning outcome criteria with the class completeness 80% that acquire the  KKM in the application of direct learning model (MPL) using the power point media in the subject Closing Journal and the Post Closing Trial Balance in XI class of SMA Muhammadiyah 4. This study is a class action research (PTK) that done in two cycles. There are four steps in each cycle; planning, execution, observation, and reflection. The data gathering technique is done trough the documentation, observation, test and questionnaire. In this study, the writer employs the quantitative descriptive analysis. The result of this study are; (1) on the observation activities toward the teachers activities in the 1 cycle to the 2nd  cycle is increased, in the 1st cycle the result is 41 and the percentage is 60,29% means good enough while the total mark in the 2nd cycle is 61 and the percentage is 89,70% that categorized as very good. (2)  in the observation activities toward the students activities are increased from the 1st cycle to the 2nd cycle. The total mark in the 1st cycle is 16 and the percentage is 57,14% that is categorized as good enough. (3) in the students test result theres the enhancement from the 1st cycle to the 2nd cycle, that is the class average mark in the 1st cycle is 70,2, while in the 2nd cycle is 78. And (4) in the students learning outcome criteria, theres an enhancement from the 1stcycle to the 2nd cycle that is; there are 16 students got the percentage of class completeness 64% has acquired the KKM, while in the 2 cycle are 23 students with the class completeness percentage is 92% has acquired the KKM.